Gulf ribbed mussels increase plant growth, primary production, and soil nitrogen cycling potential in salt marshes - Rossi, Ryann E (Marine ecology progress series, 2022)
Smooth cordgrass Spartina alterniflora and Atlantic ribbed mussels Geukensia demissa have a mutualism whereby S. alterniflora provides substrate and shade for G. demissa while G. demissa enhances S. alterniflora growth and drought tolerance. Together, these species im prove salt marsh stability and function. To better understand if a similar relationship exists between S. alterniflora and Gulf ribbed mussels G. granosissima in salt marshes of the Gulf of Mexico, we conducted a manipulative experiment with identical starting plant density and varying densities of G. granosissima and monitored plant and soil responses over a growing season. We found that S. alterniflora stem and leaf density was 1.5 and 1.9 times greater for the highest mussel biomass compared to the lowest mussel biomass treatments. Similarly, above- and below-ground biomass were 2.6 and 3.2 times greater for the highest mussel biomass compared to the lowest mussel biomass treatments. More and larger S. alterniflora at higher G. granosissima densities resulted in 2 and 4 times the S. alterniflora gross CO2 uptake and respiration rate, respectively. Methane fluxes were highest when G. granosissima were present, likely driven by the positive relationship between methane flux and belowground biomass. Net potential nitrification was 5 times higher for the highest mussel biomass compared to the lowest mussel biomass treatments, and denitrification rates were 1.8 times higher. Ultimately, our results suggest that G. granosissima increases S. alterniflora growth and productivity, much like the positive relationship between G. demissa and S. alterniflora, which in turn influences salt marsh stability and function